Factors associated with the perception of inadequate sanitary control in 12 Latin American countries during the COVID-19 pandemic - Christian R. Mejia; Christian R. Mejia; Daniela Liendo-Venegas; Fernanda García-Gamboa; Miguel A. Mejía-Rodríguez; Mario J. Valladares-Garrido; Mario J. Valladares-Garrido (Frontiers Media S.A., 2022)
IntroductionSanitary control mechanisms differ greatly from country to country. Therefore, it is important to know citizens' perception of different realities. We aimed to determine the factors associated with the perception of inadequate sanitary control in 12 Latin American countries during the COVID-19 pandemic.MethodsThis is an analytical cross-sectional study. We asked about six perceptions in regard to different situations experienced by inhabitants of 12 Latin American countries during the pandemic. Frequencies according to country were described and associations vs. other important variables were obtained.ResultsOut of 8,489 participants, 68% stated that there were moments of collective hysteria. Honduras was the country that most perceived inadequate control mechanisms established by the government. Multivariate analysis showed that there were statistically significant differences among many of the countries according to the six evaluated items. The higher the level of education, the greater the perception of poor control in five of the aspects. Additionally, men had a lower perception of inadequate control. The older the age, the lower the perception of inadequate control regarding whether there was collective hysteria and shortages of basic essentials. Those with COVID-19 had a lower perception of medicine shortages.ConclusionThe population of multiple realities in Latin America have perceived a bad management of the pandemic. Citizens' perception is an important indicator of the performance of each government during the COVID-19 pandemic. This study may provide valuable information on the relationship between the effectiveness of government sanitary control and people's mental health, which ultimately helps to create objective prevention programs against post-traumatic stress disorder, depression, fear of contagion, and collective hysteria. In addition, governments could use this information to design effective mitigation plans for future unavoidable pandemic events based on the six criteria discussed here.